2019
DOI: 10.21009/biosferjpb.v12n1.34-44
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory system: designing student worksheet based on inquiry to promote 21st-century skills

Abstract: A student worksheet is one of the learning resources containing work intended for students to be more active in learning. A student worksheet is designed based - inquiry so that learning is more meaningful and student-centered. Investigation optimally involves all students' ability to search and investigate systematically, critically, logically, analytically, so that they can formulate their findings confidently. This study aims to produce student worksheet based - Inquiry with profiles and qualities that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…The results of this study indicated that the involvement of inquiry processes in learning improved understanding of concepts and developed students' thinking abilities because in inquiry students were given problems and are required to solve the problem. In solving this problem participants will be more active both in discussing and looking for learning resources (Ristanto, 2011;Pratama, 2018). This is supported by Tukidi (2011), that inquiry is an effort intended to overcome the problem of students' boredom in learning in class which is quite useful because the learning process is student-centered.…”
Section: B Students and Teacher Response To Workheet Based-inquirymentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicated that the involvement of inquiry processes in learning improved understanding of concepts and developed students' thinking abilities because in inquiry students were given problems and are required to solve the problem. In solving this problem participants will be more active both in discussing and looking for learning resources (Ristanto, 2011;Pratama, 2018). This is supported by Tukidi (2011), that inquiry is an effort intended to overcome the problem of students' boredom in learning in class which is quite useful because the learning process is student-centered.…”
Section: B Students and Teacher Response To Workheet Based-inquirymentioning
confidence: 99%
“…The role of education is necessary to create a generation that is reliable and character based. Therefore, the learning paradigm must be shifted from teacher-centered learning to student-centered learning (Djamahar et al, 2018;Ristanto, 2011;Pratama, 2018). Students must be active and be part of learning activities (Utomo, 2016;Sartono, Rusdi & Handayani, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembelajaran Ilmu Pengetahuan Alam (IPA) di sekolah dasar sering juga dikenal pembelajaran sains (Yusnaeni, Lika, & Hiul, 2019). Pembelajaran di sekolah dasar, merupakan konsep yang terpadu karena belum dipisahkan secara tersendiri seperti mata pelajaran kimia, fisika dan biologi.…”
Section: Pendahuluanunclassified
“…Bahan ajar merupakan segala bentuk bahan yang digunakan oleh guru atau peserta didik dalam proses belajar mengajar di kelas, bahan ajar tersebut berupa teks, informasi ataupun alat sehingga tercipta suasana pembelajaran yang baik (Ali & Arif, 2019). Bahan ajar memiliki jenis, bentuk, cara kerja, dan sifatnya (Yusnaeni, Lika, & Hiul, 2019;Lestari, Ristanto, & Miarsyah, 2019). Salah satu bahan ajar yaitu handout, (Fajarianingtyas, Akbar, & Herowati, 2019;Prastowo, 2012).…”
Section: Pendahuluanunclassified